Manufacturing “Terrorists”: Refugees, National Security, and Canadian Law - Sharryn J. Aiken (Refuge, 2000)
In the first part of a two-part article, the author critically evaluates the anti-terrorism provisions of Canada’s Immigration Act. The impact of these provisions on refugees is the focus of the essay, but her observations are relevant to the situation of other categories of non-citizens as well. The inquiry begins by considering international efforts to address “terrorism,” the relevance of international humanitarian law to an assessment of acts of “terror,” and the nature of contemporary discourse on “terrorism.” Next, the evolution of the current admissibility provisions in Canadian immigration law, with particular reference to refugee policy and national security, is reviewed. A brief discussion of current policy directions concludes part 1.